2016
DOI: 10.1111/mec.13833
|View full text |Cite
|
Sign up to set email alerts
|

Weak link between dispersal and parasite community differentiation or immunogenetic divergence in two sympatric cichlid fishes

Abstract: Geographical isolation, habitat variation and trophic specialization have contributed to a large extent to the astonishing diversity of cichlid fishes in the Great East African lakes. Because parasite communities often vary across space and environments, parasites can accompany and potentially enhance cichlid species diversification. However, host dispersal may reduce opportunities for parasite-driven evolution by homogenizing parasite communities and allele frequencies of immunity genes. To test for the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 100 publications
0
24
0
Order By: Relevance
“…The relationship between parasite infection and host trophic ecology might be confounded by 250 geographic variation in parasite abundance and host-parasite co-evolutionary interactions (Bell & 251 Burt, 1991;Stutz et al, 2014). Acanthocephala infections do indeed vary across the study area 252 (Raeymaekers et al, 2013;Hablützel et al, 2016; this study) but we found the confounding effect of 253 geography to be of little importance compared to the main host species effect. Ultimately, parasite 254 load will not only be influenced by ecological (exposure to propagules) but also evolutionary 255 (parasite virulence and host susceptibility) factors.…”
Section: Foraging Ecology Predicts Parasite Infection 233mentioning
confidence: 58%
“…The relationship between parasite infection and host trophic ecology might be confounded by 250 geographic variation in parasite abundance and host-parasite co-evolutionary interactions (Bell & 251 Burt, 1991;Stutz et al, 2014). Acanthocephala infections do indeed vary across the study area 252 (Raeymaekers et al, 2013;Hablützel et al, 2016; this study) but we found the confounding effect of 253 geography to be of little importance compared to the main host species effect. Ultimately, parasite 254 load will not only be influenced by ecological (exposure to propagules) but also evolutionary 255 (parasite virulence and host susceptibility) factors.…”
Section: Foraging Ecology Predicts Parasite Infection 233mentioning
confidence: 58%
“…() and Hablutzel et al . () for examples from species‐rich communities). However, there are no comprehensive studies yet of parasitism in young adaptive radiations with replicated pairs of closely related sympatric species of variable degree of differentiation within the same evolutionary lineage of hosts (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…The first prerequisite of parasite‐mediated divergent selection in natural populations is that infections differ between diverging host populations. Currently, there is a growing body of literature describing differentiated parasite infections in ecotypes or closely related species particularly in freshwater fishes (Knudsen et al ., , ; MacColl, ; Eizaguirre et al ., ; Natsopoulou et al ., ; Karvonen et al ., ,b, ) including cichlid fishes (Blais et al ., ; Maan et al ., ; Raeymaekers et al ., ; Hablutzel et al ., , ). Overall, these studies suggest that conditions for parasite‐mediated divergent selection between ecological niches are not uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Both intestinal and ectoparasites tended to be more abundant at Toby's Place and less abundant at Cape Kanwankoko. Geographical variation in parasite communities for two species of tropheine cichlids within the same study area has been reported earlier ( Tropheus moorii Boulenger 1898 and Simochromis diagramma (Günther 1894); Raeymaekers et al ., ; Hablützel et al ., ). Such variation may reflect local dynamics of spatially independent parasite populations or differences in abundances of intermediate or alternative hosts.…”
Section: Discussionmentioning
confidence: 97%